IAP dependency of T-cell prolymphocytic leukemia identified by high-throughput drug screening - Pohly, Marcel; Putzker, Kerstin; Scheinost, Sebastian; Ben Taarit, Lena; Walther, Tatjana; Kummer, Sandra; Wertheimer, Tobias; Lin, Minqi; Do, Thi Huong Lan; Handler, Kristina; Michler, Jan; Kivioja, Jarno; et al. (Blood, 2025)
T-cell prolymphocytic leukemia (T-PLL) is an aggressive lymphoid malignancy with limited treatment options. To discover new treatment targets for T-PLL, we performed high-throughput drug sensitivity screening on 30 primary patient samples ex vivo. After screening >2800 unique compounds, we found T-PLL to be more resistant to most drug classes, including chemotherapeutics, than other blood cancers. Furthermore, we discovered previously unreported vulnerabilities of T-PLL. T-PLL cells exhibited a particular sensitivity to drugs targeting autophagy (thapsigargin and bafilomycin A1), nuclear export (selinexor), and inhibitor of apoptosis proteins (IAPs; birinapant), sensitivities that were also shared by other T-cell malignancies. Through bulk and single-cell RNA sequencing, we found these compounds to activate the Toll-like receptor (bafilomycin A1), p53 (selinexor), and tumor necrosis factor α (TNF-α)/NF-κB signaling pathways (birinapant) in T-PLL cells. Focusing on birinapant for its potential in drug repurposing, we uncovered that IAP inhibitor-induced cell death was primarily necroptotic and dependent on TNF-α. Through spectral flow cytometry, we confirmed the absence of cleaved caspase-3 in IAP inhibitor-treated T-PLL cells and show that IAP inhibition reduces the proliferation of T-PLL cells stimulated ex vivo, while showing only a limited effect on nonmalignant T-cells. In summary, our study maps the drug sensitivity of T-PLL across a broad range of targets and identifies new therapeutic approaches for T-PLL by targeting IAPs, exportin 1, and autophagy, highlighting potential candidates for drug repurposing and novel treatment strategies.